Penguatan Peran Keluarga Dalam Perawatan Pasien Stroke Melalui Edukasi Home Care Oleh Perawat Komunitas - Sallo, Andi Kamal M.; Betan, Abu Bakar; Noyumala, Noyumala; Noviar, Rizki Andita; Lestari, Ima Mustika Tri (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Stroke is a leading cause of disability and long-term dependency in patients, especially in the elderly. In the context of post-stroke recovery, home care plays a crucial role in supporting rehabilitation and improving patients' quality of life. However, families' limited knowledge and skills in caring for stroke patients often pose a major obstacle to the recovery process. This community service activity aims to strengthen the role of families in caring for stroke patients through home care education provided by community nurses. The activity included counseling, practical demonstrations, interactive discussions, and direct support for 20 families of stroke patients in the working area of Community Health Center X. Results showed a significant increase in knowledge, basic care skills, and family confidence after participating in the education. This activity demonstrates the strategic role of community nurses in family empowerment and spearheads the success of community-based home care programs. Sustainability of the program and cross-sectoral involvement are highly recommended to expand its impact.